Measuring Performance of Rainwater Energy by Using Piezoelectric Sensors with Arduino Uno Microcontroller in Actual Rainfall - Zaabah A.R.; Omar M.A.; Zakaria N.M.; Ramli A.B.; Mukhtar A. (American Institute of Physics, 2025)
The development of microelectronics has led to smaller appliances. These appliances can now be fed from energy recovered by an energy harvester. The piezoelectric harvester can be utilized to convert vibrations into electricity. Thus, when raindrops have an impact on the surface of a piezoelectric beam, the stress energy generated by the penetrating raindrop will be converted into harvestable electrical energy. Most of the studies were performed by simulating rain droplets using laboratory devices that are not completely accurate with respect to the actual rain situation. The novelty of this study is to examine the energy produced in the actual rainfall where the intensity of the rain is contemplated. This study examined the power collection performance of rainwater using a piezoelectric sensor in Jerteh, Terengganu. The voltages generated by the raindrops were measured using an Arduino UNO microcontroller, and an ad-hoc circuit was constructed to improve the result obtained from the raindrops. The study analysed three different timelines at the peak and at the end of the rainfall event in May 2021. The result showed that the maximum voltages of 2.68V, 3.96V and 3.35V were produced by raindrops over the three timelines. Hence, the accumulated energy could be reported at 0.12 ?J, 1.9 ?J, and 0.22 ?J, respectively. The results of this study indicate that utilising this strategy, the quantity of energy created by actual rainfall is minimal. However, it is still advantageous for supplying energy to low-power micro electron devices. ? 2024 American Institute of Physics Inc.. All rights reserved.